Area-selective atomic layer deposition of Ru on electron-beam-written Pt(C) patterns versus SiO2 substratum. (6th September 2017) - Junige, Marcel; Löffler, Markus; Geidel, Marion; Albert, Matthias; Bartha, Johann W; Zschech, Ehrenfried; Rellinghaus, Bernd; Dorp, Willem F van
Abstract: Area selectivity is an emerging sub-topic in the field of atomic layer deposition (ALD), which employs opposite nucleation phenomena to distinct heterogeneous starting materials on a surface. In this paper, we intend to grow Ru exclusively on locally pre-defined Pt patterns, while keeping a SiO2 substratum free from any deposition. In a first step, we study in detail the Ru ALD nucleation on SiO2 and clarify the impact of the set-point temperature. An initial incubation period with actually no growth was revealed before a formation of minor, isolated RuO x islands; clearly no continuous Ru layer formed on SiO2 . A lower temperature was beneficial in facilitating a longer incubation and consequently a wider window for (inherent) selectivity. In a second step, we write C-rich Pt micro-patterns on SiO2 by focused electron-beam-induced deposition (FEBID), varying the number of FEBID scans at two electron beam acceleration voltages. Subsequently, the localized Pt(C) deposits are pre-cleaned in O2 and overgrown by Ru ALD. Already sub-nanometer-thin Pt(C) patterns, which were supposedly purified into some form of Pt(O x ), acted as very effective activation for the locally restricted, thus area-selective ALD growth of a pure, continuous Ru covering, whereas the SiO2 substratum sufficiently inhibited towards no growth. FEBID at lower electron energy reduced unwanted stray deposition and achieved well-resolved pattern features. We access the nucleation phenomena by utilizing a hybrid metrology approach, which uniquely combines in-situ real-time spectroscopic ellipsometry, in-vacuo x-ray photoelectron spectroscopy, ex-situ high-resolution scanning electron microscopy, and mapping energy-dispersive x-ray spectroscopy.